KRITIK SANAD: SEBUAH ANALISIS KESHAHIHAN HADITS - Ulin Nuha (AN NUR: Jurnal Studi Islam, 2013)
Hadith is the source of second law of Islam. It is explanatory of the verses of the Qur’an as found in the Qur’an is not understandable language. From the verses of the Qur’an are not known the meaning clearly, then Prophet tells us with his words were later called Hadith. Therefore, Hadith has a very important role in the determination of the laws of syari’at. However, not all of Hadith could been served as a source of law. Certain only hadiths which could serve as a source of legal settlers. For example it is shahih hadiths.To note here is how to tell a shahih hadeeth that or dla’if. The problem of this paper to present to discuss and find out whether a hadeeth shahih or dla’if. With the example of hadeeth which speaks of “ Prophet’s intercession for his people”, we will to find out how do I do to find out if the isnaad critique a shahih hadeeth that or dla’if. The steps that should be taken in the criticism is isnaad; First, do i’tibar Hadith. Second, examine the quality of and methods have. And the third is to determine the outcome of the first and second steps that have been taken. Research of sanad criticism has with regard to the hadeeth which discuss of “the Prophet’s intercession for his people”, that is after doing i’tibar Hadith and examine the quality of the rawi have produced quality a shahih isnaad as-isnaad.